Polymyxin-resistant, carbapenem-resistant Acinetobacter baumannii is eradicated by a triple combination of agents that lack individual activity. (28th February 2017) - Lenhard, Justin R.; Thamlikitkul, Visanu; Silveira, Fernanda P.; Garonzik, Samira M.; Tao, Xun; Forrest, Alan; Soo Shin, Beom; Kaye, Keith S.; Bulitta, Jürgen B.; Nation, Roger L.; Li, Jian; Tsuji, Brian T.
Abstract : Objectives: The emergence of polymyxin resistance threatens to leave clinicians with few options for combatting drug-resistant Acinetobacter baumannii . The objectives of the current investigation were to define the in vitro emergence of polymyxin resistance and identify a combination regimen capable of eradicating A. baumannii with no apparent drug susceptibilities. Methods: Two clonally related, paired, A. baumannii isolates collected from a critically ill patient who developed colistin resistance while receiving colistin methanesulfonate in a clinical population pharmacokinetic study were evaluated: an A. baumannii isolate collected before (03-149.1, polymyxin-susceptible, MIC 0.5 mg/L) and an isolate collected after (03-149.2, polymyxin-resistant, MIC 32 mg/L, carbapenem-resistant, ampicillin/sulbactam-resistant). Using the patient's unique pharmacokinetics, the patient's actual regimen received in the clinic was recreated in a hollow-fibre infection model (HFIM) to track the emergence of polymyxin resistance against 03-149.1. A subsequent HFIM challenged the pan-resistant 03-149.2 isolate against polymyxin B, meropenem and ampicillin/sulbactam alone and in two-drug and three-drug combinations. Results: Despite achieving colistin steady-state targets of an AUC0–24 >60 mg·h/L and C avg of >2.5 mg/L, colistin population analysis profiles confirmed the clinical development of polymyxin resistance. During the simulation of the patient's colistin regimen in the HFIM, no killing was achieved in the HFIM and amplification of polymyxin resistance was observed by 96 h. Against the polymyxin-resistant isolate, the triple combination of polymyxin B, meropenem and ampicillin/sulbactam eradicated the A. baumannii by 96 h in the HFIM, whereas monotherapies and double combinations resulted in regrowth. Conclusions: To combat polymyxin-resistant A. baumannii, the triple combination of polymyxin B, meropenem and ampicillin/sulbactam holds great promise.